Effects of Ginsenoside Rg(3) on alpha 9 alpha 10 Nicotinic Acetylcholine Receptor-Mediated Ion Currents - Lee, Byung-Hwan; Choi, Sun-Hye; Hwang, Sung-Hee; Kim, Hyeon-Joong; Lee, Sang-Mok; Kim, Hyoung-Chun; Rhim, Hyewhon; Nah, Seung-Yeol (PHARMACEUTICAL SOC JAPAN, 2013)
Ginsenosides is a low molecular weight substance found in ginseng as one of the active ingredients. Ginsenosides, like other herbal medicines, has a wide range of neuropharmacological actions including neuroprotective effects. The alpha 9 alpha 10 nicotinic acetylcholine receptor is one of numerous nicotinic acetylcholine receptors that exists as a heteropentameric form in auditory hair cells of the cochlea. In this study, we report the effects of ginsenosides on rat alpha 9 alpha 10 nicotinic acetylcholine receptor-mediated ion currents using the two-electrode voltage clamp technique. Treatment with acetylcholine evoked inward currents (I-Ach) in oocytes heterologously expressing the alpha 9 alpha 10 nicotinic acetylcholine receptor. Ginsenosides blocked I-Ach in order of potency of Rg(3)> Rb-2> CK>Re=Rg(2)> Rf>Rc> Rb-1> Rg(1) with reversible manners, and the blocking effect of Rg(3) on I-Ach was same after pre-application than co-application of Rg(3)(-). The half maximal inhibitory concentration (IC50) of Rg(3) was 39.6 +/- 4.9 mu M. Rg(3)-induced I-Ach inhibition was not affected by acetylcholine concentration and was independent of membrane holding potential. Although the inhibitory effect of Rg(3) on I-Ach was abolished in oocytes expressing alpha 9 subunit alone, indicating that the presence of alpha 10 subunit might be required for Rg(3)-induced regulations of alpha 9 alpha 10 nicotinic acetylcholine receptor channel activity. These results indicate that alpha 10 subunit of alpha 9 alpha 10 nicotinic acetylcholine receptor might play an important role in Rg(3)-induced regulation of the alpha 9 alpha 10 nicotinic acetylcholine receptor.
Keywords: CENTRAL-NERVOUS-SYSTEM; COCHLEAR HAIR-CELLS; CHOLINERGIC-RECEPTOR; SUBUNIT; ALPHA-10; FAMILY